2001
DOI: 10.1109/32.908961
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing symbolic model checking for statecharts

Abstract: AbstractÐSymbolic model checking based on binary decision diagrams is a powerful formal verification technique for reactive systems. In this paper, we present various optimizations for improving the time and space efficiency of symbolic model checking for systems specified as statecharts. We used these techniques in our analyses of the models of a collision avoidance system and a faulttolerant electrical power distribution (EPD) system, both used on commercial aircraft. The techniques together reduce the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 38 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…Chan et al [1998] have defined an algorithm for slicing RSML models for model checking. They have experimentally evaluated their slicing approach in Chan et al [2001] on two models, the TCAS II model [Heimdahl and Leveson 1995] and Boeing EPD (Electrical Power Distribution) case study [Nobe and Bingle 1998]. Results show that applying slicing to TCAS II reduces the Boolean state variables by half for four of the five properties.…”
Section: Model Checkingmentioning
confidence: 98%
See 1 more Smart Citation
“…Chan et al [1998] have defined an algorithm for slicing RSML models for model checking. They have experimentally evaluated their slicing approach in Chan et al [2001] on two models, the TCAS II model [Heimdahl and Leveson 1995] and Boeing EPD (Electrical Power Distribution) case study [Nobe and Bingle 1998]. Results show that applying slicing to TCAS II reduces the Boolean state variables by half for four of the five properties.…”
Section: Model Checkingmentioning
confidence: 98%
“…The slicing algorithm [Chan et al 2001] is not minimal and may include false dependencies, that is, elements are shown to be dependent on each other when they should not be. Not only do false dependencies increase the size of the slice but they can mislead as to which elements actually affect the slicing criterion.…”
Section: Proposition-based Slicingmentioning
confidence: 99%
“…Microstep visibility has been used in (Chan et al, 2001), though for different purposes that are not directly applicable to our approach. These authors use a microstep counter to optimise the analysis of statechart-like specifications, making every macrostep equal in length to prune backward searches in BBD-based model checking.…”
Section: Microstep Countermentioning
confidence: 99%
“…For example, model checking frameworks have been applied to reason about software process models (e.g., [25]), software requirements models (e.g., [5]), architectural frameworks (e.g., [19,26]), design models (e.g., [1,22]), and system implementations (e.g., [3,8,20]). The effectiveness of these efforts has in most cases relied on detailed knowledge of the model checking framework being applied.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of these efforts has in most cases relied on detailed knowledge of the model checking framework being applied. In some cases, a new framework was developed that was targeted to the semantics of a family of artifacts [3,20], while in other cases it was necessary to study an existing model checking framework in detail in order to customize it [5,10]. Unfortunately, this level of knowledge and effort currently prevents many domain experts from successfully applying model checking to software analysis.…”
Section: Introductionmentioning
confidence: 99%